The Relationship Between Dietary Fiber Consumption and The Incidence of Obesity in Students of The Faculty of Medicine, Universitas Sumatera Utara - Binti Iqbal, Nurun Nabilah; Martineta, Meriza; M Rambe, Andrina Yunita; Siregar, Muhammad Fidel Ganis (Buletin Farmatera, 2022)
Abstract. Obesity is caused by the changes in nutrient intake due to changes in diet by populations who have adopted a modern lifestyle, thus increasing the tendency of fat consumption with decreased consumption of fiber and lack of physical activity. The role of fiber in obesity includes helps indigestion and helps to reduce the occurrence of obesity. This study aims to determine the relationship between dietary fiber consumption and the incidence of obesity in students of the Faculty of Medicine, Universitas Sumatera Utara. This research is analytic observational research with a cross-sectional design. The sample was selected using a non-probability sampling technique, with a sample size of 72 people. The measuring instrument used is a questionnaire. From table 4.4 the research subjects are 72 respondents; 11 respondents are grouped in underweight nutritional status and all 11 respondents have insufficient fiber consumption. There are 29 respondents who are grouped in a normal nutritional status where 8 respondents have sufficient fiber consumption and 21 respondents have insufficient fiber consumption. A total of 12 respondents were classified as overweight, 7 of the 12 respondents have sufficient fiber consumption and 5 respondents have insufficient fiber consumption. There are 20 respondents grouped in the nutritional status of obesity, 10 respondents whose fiber consumption is sufficient, and 10 respondents whose fiber consumption is insufficient. From the results of the Spearman correlation test, a p-value of 0,049 was obtained and the RR value was -0,233. There is a weak and unidirectional relationship between dietary fiber consumption and the incidence of obesity in students of the Faculty of Medicine, Universitas Sumatera Utara.Keywords: Dietary fiber, obesity, students